Website-Based Photo Studio Information System for Customer Reservation Management - Fatimah Az-Zahra; Auliya Zenita Rachman, Annisa; Hanifah, Hana; Vernanda, Dwi (Expert Net: Exploration Journal of Technological Education Trends, 2025)
The development of information technology has changed the way interactions and transactions occur in the photography industry, where many photo studios face challenges in accessing service information, administrative efficiency, and transaction management. This research aims to develop a Website-Based Photo Studio Information System that can improve service quality and operational efficiency. The method used is the Software Development Life Cycle (SDLC) with the waterfall model, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The results of the research show that the developed system allows customers to access service information, make online bookings, and simplifies administrative management for service providers. With this system, customers can make reservations anytime and anywhere, thereby reducing queues at the location and enhancing the customer experience. In addition, this system also helps service providers manage order data, transactions, and reports, thereby minimizing errors and increasing efficiency. The implementation of this web-based information system is expected to serve as a model for other small businesses in utilizing technology to enhance service and competitiveness in the digital era.